Optical Devices Constructed From Responsive Microgels for Polyphenols Detection - Wang, Jingying; Zhang, Xieli; Shi, Kaiyao; Zhang, Qiang (Frontiers in Chemistry, 2021)
Polyphenols are used as antioxidants in various foods and beverages, which are considered to be a health benefit. The measurement of polyphenols contents is of great interest in food chemistry and health science. This work reported a microgels based photonic device (etalon) to detect polyphenols. Dopamine was used as a model compound of polyphenols. Herein, we proposed a “block” concept for dopamine detection. The dopamine was oxidized and formed dopamine films catalyzed by tyrosine on the surface of etalon. As the etalon was immersed in ZnCl2, the dopamine films blocked the ZnCl2 diffusion into etalon that caused optical property changes. The film thickness is associated with the concentration of dopamine which can be readout via optical signals.